An analysis of EAGLEs: emerging and growth-leading economies - Marques, Inês Maria Aparício (2015)
Globalization opened up immense opportunities in many fields, with countries increasingly integrated and, consequently, contributing for world economic development. There are nations – developed countries – more evolved than others – developing countries, mostly due to the strong control policies, where government agencies play a central role in economy. But these trends are changing and the emerging nations are making advances towards liberalization, privatization and legislative changes. EAGLEs (Emerging And Growth-Leading Economies) is an acronym created by the BBVA Research and designates a group of countries which are considered as emerging countries. It is important to mention that the pertinent report is revised yearly, thus providing an updated analysis and a greater credibility. In 2012, 9 nations were considered EAGLE: Brazil, China, India, Indonesia, Mexico, Russia, South Korea, Taiwan and Turkey. In this work was made a comparative analysis was made of the countries listed, namely was performed a PESTEL analysis, in order to verify if an EAGLE should be regarded as emerging or advanced country. After a deep examination of 100 important indicators, covering all categories of PESTEL, it came to conclusion that South Korea and Taiwan must be considered as developed and, therefore, must be excluded from EAGLE. Indeed, there are major differences in some topics between 2 EAGLEs (South Korea and Taiwan) vs 7 EAGLEs (Brazil, China, India, Indonesia, Mexico, Russia and Turkey) and, in order to defend the theory that both countries must be presented as developed, a comparison with other advanded markets, by 2014 International Monetary Fund classification, is take into account in this thesis.